Effects of Varicocelectomy on Serum Testosterone Levels among Infertile Men with Varicocele - Jangkhah, Meysam (Int J Fertil Steril, 2018)
BACKGROUND: The main purpose of this study is to evaluate the effects of varicocelectomy on serum testoster- one levels and semen quality in infertile men who suffer from varicocele. MATERIALS AND METHODS: This prospective study enrolled 115 subjects with clinical varicocele grades II and III and 240 fertile men as the control group. Total volume of testosterone serum level (ng/dl) and semen quality were com- pared before and after microscopic varicocelectomy. We normalized testosterone serum levels for age, grade, and testis size basis. SPSS 20 software was used to analyze the data. All results of continuous variables were reported as mean ± SD. Statistical significance was set at a P<0.05. RESULTS: The mean ages of individuals who participated in the treatment (32.2 ± 5.23) and control (32.8 ± 5.27) groups were similar. There were similar mean values for adjusted testosterone levels between the varicocele (567 ± 222 ng/ml) and control (583 ± 263 ng/ml) groups. In the varicocele group, the adjusted testosterone levels insig- nificantly increased to 594 ± 243 ng/ml. Among semen parameters, only mean sperm concentration significantly increased after varicocelectomy. CONCLUSION: Despite increases in sperm concentration, adjusted testosterone levels did not significantly improve after varicocelectomy.